2023
DOI: 10.1016/j.prosdent.2021.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Process parameter optimization for removable partial denture frameworks manufactured by selective laser melting

Abstract: Removable partial denture (RPD) frameworks have been traditionally produced with the lost-wax casting technique, although the process is complex because the metal is melted at around 1400 C and the emission of toxic gasses requires a rigorous safety protocol. 1 The accuracy and reliability of RPD framework production can be problematic. 2 In the past 20 years, digital technologies have improved in accuracy, reliability, and repeatability, and currently computer-aided design and computer-aided manufacturing (CA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 29 publications
(34 reference statements)
0
12
0
Order By: Relevance
“…The study by Gong et al (2014) showed that the porosity of Ti–6Al–4V parts built with a 1,200-mm/s laser speed and 80-W laser power was more than 5%. However, Hwang et al (2021) showed that the porosity of CP Ti parts built with a 1,200-mm/s scan speed and 90-W power was 0.81%. The density and porosity have direct effects on the resiliency and fatigue properties of clasps.…”
Section: Resultsmentioning
confidence: 97%
See 3 more Smart Citations
“…The study by Gong et al (2014) showed that the porosity of Ti–6Al–4V parts built with a 1,200-mm/s laser speed and 80-W laser power was more than 5%. However, Hwang et al (2021) showed that the porosity of CP Ti parts built with a 1,200-mm/s scan speed and 90-W power was 0.81%. The density and porosity have direct effects on the resiliency and fatigue properties of clasps.…”
Section: Resultsmentioning
confidence: 97%
“…In this experiment, single prism support structures should be replaced by lightweight ones (Calignano, 2014), for example, tree supports. It is necessary to orientate maxillary RPD frameworks and apply proper support structures to reduce the overhang surface area of clasps' intaglio surface, the residual stress and the deformation of maxillary RPD frameworks (Hwang et al, 2021). The build orientation affects the accuracy of the intaglio surface of RPD frameworks, the fatigue strength of clasps (Xie et al, 2020;Kajima et al, 2018), and the building efficiency of RPD frameworks.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this manufacturing process is still under development, expensive and rarely found in prosthetic laboratories. 5 7 8 Hwang et al 9 have optimized the SLS printing process and found that the transverse build angle and inter-connected support structure had the best accuracy (167 ± 105 µm) and optimum density, surface roughness, and productivity, compared to the other studying groups. SLS was also appraised in the literature on its ability to manufacture RPD with a range of accuracy (166 ± 9 to 123 ± 9 µm).…”
Section: Introductionmentioning
confidence: 99%